ESL students’ interaction in social networking site via facebook: a case study in UiTM Cawangan Johor / Diana Othman - Othman, Diana (2014)
This study investigates ESL students’ interaction via Facebook group discussion. A convenient sampling was used to select 30 diploma students of Computers and Mathematical Sciences in UiTM Cawangan Johor. The finding reported that most students showed positive attitude towards the use of Facebook group discussion in their language learning process. The findings also recorded that the students possessed high motivational intensity to learn English despite the existence of the other two factors of language anxiety and attitude towards learning English. As for the use of Facebook group discussion, the students reflected to have agreed that the use of the social networking site has helped them in their language learning. Students responded to have optimistic views on the use of Facebook group discussion in terms of improving their language skills, in terms of its convenience and the student’s preferences. Therefore, all these teaching and learning experiences of using Facebook group discussion in encouraging participation among ESL students can lead to important implications purposes for effective teaching and learning strategies.